(untitled) (Indian Journal of Fibre & Textile Research (IJFTR), 2025)
This study evaluates the performance of inherent flame-retardant (FR) fabrics under low-pressure steam exposure and characterises their response to hot surfaces, convective and radiant heat, and molten aluminium—one of the most common industrial hazards in India. The investigation compares FR-treated cotton, 100% para-aramid fabric (325 g/m²), and Savesplash® fabric (550 g/m²), a blend of FR viscose, para-aramid, and high-shrink PVC fibre. The fabrics are coated with neoprene on one side using the knife roller coating method. Results indicate that Savesplash® outperforms 100% para-aramid fabric in convective, radiant and contact heat resistance due to its higher thickness and weight. In the case of molten aluminium, both fabrics demonstrate superior performance when the molten aluminium is poured onto the coated side. However, under low-pressure steam conditions of 3 bar at 120⁰C, 100% para-aramid exhibits better resistance than Savesplash®. Further research is required to assess aluminised fabrics under higher temperatures, increased steam pressure, and varied molten metal exposures.